MENGATASI KEJENUHAN PEMBELAJARAN DARING MELALUI KONSELING RATIONAL EMOTIF THERAPY PADA SISWA SMK NEGERI 3 PATI - Steffani Fabela Ardiyanti; Edris Zamroni; Masturi Masturi (Universitas Muria Kudus, 2022)
The objectives of this study are: 1) To describe the factors that cause online learning saturation in class XI majoring in catering services for the 2020/2021 academic year. 2) Helping overcome the saturation of online learning in class XI of the culinary service of SMK Negeri 3 Pati for the 2020/2021 academic year through Rational Emotive Therapy counseling.Based on the results of the study, it shows that after the counselee is given Rational Emotive Therapy Counseling, it can be seen that the cause is the counselee who is bored with online learning because he procrastinates on assignments and thinks there is no point in doing assignments if he doesn't understand the material, so that the counselee is left behind in a lot of subject matter and has a negative impact. on student grades. For this reason, counselors apply Rational Emotive Therapy counseling so that they can overcome student boredom during online learning.